Remoção de fármacos por adsorção através de compósitos sintetizados a base de quitosana - Machado, Thaís Strieder (2022)
Emerging contaminants are a category of compounds that have received attention in relation to effluent treatment techniques, standing out drugs and their metabolites, due to the adverse risks they can cause to the ecosystem. In this way, adsorption is a technique that has the potential for the removal of these contaminants, but the search for materials with physical and chemical properties favorable to the removal of emerging compounds is a challenge. Chitosan can be obtained from fishing residues and extracted from microorganisms, with recognized adsorption capacity, but which has some limitations. The development of chitosan-based composites is a necessity in order to overcome its shortcomings, having as alternatives for the development through the sol-gel technique and the use of crosslinkers. In addition to these possibilities, the increase in adsorption capacity through the use of biosurfactants in the synthesis of adsorbent composites is a gap in the state of the art. Thus, this study aimed to develop chitosan-based composites using the sol-gel technique for the removal of drugs present in water through adsorption and aided by bacterial biosurfactants. Crustacean chitosan was obtained from shrimp shells using thermochemical deacetylation in a reactor with total open reflux and fungal chitosan through an autoclave process. The synthesis of the composites took place through the sol-gel technique using tetraethoxysilane (TEOS) as a silica precursor and promoting chemical modifications through crosslinking with glutaraldehyde in different proportions. The addition of biosurfactants in the synthesis of adsorbents was evaluated using different proportions of rhamnolipid in relation to chitosan mass. The composites developed were characterized through physical and chemical analyses. The adsorbents were evaluated against the adsorption of sodium diclofenac and amoxicillin in aqueous solutions through batch isothermal and kinetic profiles determinations. Studies of desorption and reuse of adsorbents were also carried out. Finally, the fixed bed adsorption was conducted using a simulated hospital effluent, in order to evaluate the behavior of the adsorbent developed in a process similar to the real one. Crustacean chitosan reached a degree of deacetylation equal to 85% and fungal chitosan 61.92%. The adsorbent composites synthesized with crustacean chitosan (D-glucosamine) cross-linked with glutaraldehyde and silica showed improved physical and chemical characteristics. Through the sodium diclofenac adsorption assays, the adsorbent with D-glucosamine and glutaraldehyde of 1:8, stood out with 237.8 mg/g due to the effect of the crosslinker’s autopolymerization. When evaluated in the adsorption of amoxicillin, this composite obtained 97.4 mg/g and showed a promising life cycle. When applied in the treatment of simulated hospital effluent, it presented an overall removal of 56.48% and the ability to auxiliary to reduce the concentration of chemical demand for oxygen, phosphorus, nitrogen, turbidity and color. The concentration of 30% of rhamnolipid in the 1:0 composite provided an increase of 143.6 mg/g in the adsorption capacity of diclofenac sodium. The substitution of chitosan from crustaceans by the fungal in the synthesis of materials presented adsorption of sodium diclofenac of 115.5 mg/g in the composite 1:8 from fungal chitosan. Therefore, adsorbent composites obtained from chemical modifications were able to remove emerging contaminants with potential for real applications.